Utilizing the biosimulator to analyze the environmental microbiome within the intensive care units of a hospital - Sunil Thomas; Kyle Bittinger; Lawrence L. Livornese (BioTechniques)
Hospital-acquired infections (HAIs), also known as nosocomial infections, are illnesses contracted during treatment at a healthcare facility and can result in severe or life-threatening complications. HAIs are caused by microorganisms that exhibit resistance to standard antibiotics. HAIs can lead to severe complications, longer stays, and increased mortality, particularly in vulnerable patients. In our previous study, we demonstrated the ability of an engraved Petri dish, referred to as a “biosimulator,” to induce adhesion of non-adherent cells and the microbiome. This paper explores the use of the biosimulator to elucidate the microbiome composition within intensive care units (ICUs) in a hospital setting. The biosimulator, with a nutrient-rich bacterial growth medium, was placed in ICUs for 24 h, then incubated for three days under aerobic and anaerobic conditions. Using 16S rRNA sequencing, we profiled the ICU microbiome from multiple samples. Our findings showed that ICU microbiomes closely mirrored those of patients, with microorganisms in the ICU exhibiting stronger interrelationships than in control conditions. The combined use of the biosimulator and profiling offers an effective approach for analyzing and understanding microbiome changes in healthcare settings, particularly in high-risk areas, such as ICUs.